Deteksi Dini Gangguan Paru di Wilayah Rawan Polusi: Implementasi Spirometri sebagai Alat Skrining Masyarakat - Susy Olivia Lontoh; Santoso, Alexander Halim; Gunaidi, Farell Christian; Averina, Frilliesa; Setia, Nicholas (STIKes Ibnu Sina Ajibarang, 2025)
Pulmonary function disorders such as asthma and chronic obstructive pulmonary disease (COPD) remain major public health challenges, particularly in densely populated urban areas like Kapuk, Cengkareng, which are characterized by high exposure to air pollution and smoking habits. Early detection using spirometry is a crucial preventive strategy to identify respiratory dysfunction before the onset of clinical symptoms. This community engagement program aimed to conduct lung function screening using spirometric evaluation, focusing on the FEV1/FVC ratio (FEV1%) as a primary indicator. The program was conducted in Kapuk, Cengkareng, involving 64 participants from the public. Spirometry was used to measure Vital Capacity (VC), Forced Vital Capacity (FVC), Forced Expiratory Volume in 1 Second (FEV1), and the FEV1/FVC ratio. Activities began with community outreach, participant registration, brief anamnesis, and standardized spirometry procedures performed by trained health professionals. The results were immediately shared with participants along with individualized health education. Most participants were female (68.7%), with a mean age of 41.86 years. The average VC was 2.62 L, FVC 2.36 L, and FEV1 2.10 L. The mean FEV1/FVC ratio (FEV1%) was 91.66% (SD = 8.07), indicating that all participants (100%) had normal pulmonary function. These findings demonstrate that spirometry effectively provides an objective overview of respiratory health status and serves as a preventive monitoring tool. Spirometry-based pulmonary screening represents an effective preventive intervention to increase community awareness of respiratory health. The FEV1% value has been proven to be a vital parameter for early assessment of lung function. This program offers a replicable model for community-based early detection strategies in other high-risk urban areas. Keywords: Spirometry, FEV1%, Lung Function, Early Detection, Community Service